Istilah-Istilah dalam Upacara Minum Teh Jepang Chanoyu (Suatu Kajian Etnolinguistik) - Irzam Sarif S.; Susi Machdalena (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
Chanoyu is a popular culture today even though this culture has been around for a long time. This study aimed to describe the problem of terms, especially their relationship with the culture of the speakers in the chanoyu procession. This research was a qualitative descriptive study. The approach used was an ethnolinguistic approach. The result of this research showed that the tea ceremony has become an important part of Japanese culture. The terms found in the procession indicate that the guest and the host respect each other and give meaning to the journey of life. The use of terms in the lexicon in the tools used is also seen in terms of form, its manufacture and use creates perfect harmony in the chanoyu process.